A Case Report of a Patient with Turner Syndrome, Multiple Comorbidities, and Pustular Psoriasis: Correlation or Coincidence?. (8th January 2020) - Egger, Andjela; Maderal, Andrea; Lev-Tov, Hadar; Stojadinovic, Olivera
Abstract : Turner syndrome (TS) is one of the most common chromosomal abnormalities. Patients with TS are at an increased risk for the development of metabolic syndrome, hypertension (HTN), diabetes mellitus type II (DM2), hyperlipidemia (HLD), obesity, and cardiovascular disease. The association between psoriasis and the aforementioned conditions including metabolic syndrome, HTN, HLD, obesity, and cardiovascular disease has also been established. Although the mechanism for heightened risk in TS patients is yet to be elucidated, patients suffering from TS and cardiometabolic diseases are likely to be at an even higher risk for developing psoriasis than patients suffering from TS alone. We present a case of a 53-year-old Hispanic woman with a mosaic TS and multiple comorbidities who presented with pustular psoriasis. For this patient, management can be challenging considering her numerous medical comorbidities and the presence of both TS and psoriasis.